Histórias e memórias da vida em comunidade: os processos sociais de educação entre descendentes de ucranianos em Jesuíno Marcondes, Prudentópolis – PR - ZAZULA, MARIELLE (2016)
The objective of this dissertation is to discuss and to analysis social practices which members from Jesuíno Marcondes rural community in Prudentópolis, Paraná have composed their experiences, knowledge, culture and identity, in other words, their education. We decided to hear older people’s memories who has lived during more years in the community to know widespread practices. In middle of many possibilities of oral history we chose life histories since we believe they are not only learnt in schools but during all existence. In these terms, own life histories are education memories because everything people told was learnt in some moment in their life. Hearing these histories also was to save the social history of the community to be not forgotten. Histories were told by members who take part of the popular layer in socioeconomic hierarchy. So to hear these life histories was a political action because it helps to construct a more democratic History trying to break the dominant ideology that generally only considers as important what the wealthy layer thinks is progress ignoring common people’s memories that take part of the History and are skipped. Our objective was to demonstrate that common people also are part of the History as alive and kicking people in this process. It is important to say that the studied community was colonized by Ukrainian immigrants between the end of 19th century and beginning of 20th century and until nowadays descendants hold their mores and beliefs that compose their identity. These immigrants did not come alone, they took part of a wide contingent of ethnicities arrived in Brazil during the period called “the big immigration” (1860-1930). In general, our text is divided in four fundamental parts. In the first chapter we talked about the big immigration specifically the Ukrainian immigration to Prudentópolis and the constitution of the Jesuíno Marcondes rural community. In the second chapter we talked about the methodology of this research, the memories and life histories. In the third chapter we presented six complete transcriptions of life histories heard from members of the community. In the last chapter, in middle of unending possibilities of analysis of these memories, we chose the category education which one we understand it is more than just schools. Results were, although some limits, memories contribute to historical reconstruction of spaces and collective practices carried out in the part. It gives important information to analysis and researches about education.